Campus Website Security Vulnerability Analysis Using Nessus - Muhammad Abdul Muin; Kapti Kapti; Tri Yusnanto (Institut Teknologi Bisnis AAS Indonesia, 2022)
Agencies or organizations are competing to create websites for their agencies, where this website to make work easier or disseminate information to the public in this study is a college or campus website. With this website, many people access it, so there is a possibility of security holes, which can be exploited by irresponsible people. So that data can be manipulated, retrieved or otherwise to the detriment of one-sided or several parties. For this reason, we tried to analyze the vulnerability of a website using a software called Nessus. From the results of the scan, it was found that several vulnerabilities were found from each website with different vulnerability levels. Of the 3 websites that have the most vulnerabilities, web 1 is 14. Meanwhile, the vulnerability at the medium level is on web 2, which is 22%. For the vulnerability lies in a weak DNS Server.